Potential customer intention to buy Amanah Saham 1 Malaysia: case study in Melaka / Nor Hafizah Md Salleh - Md Salleh, Nor Hafizah (Faculty of Business and Management, 2009)
Customer intention to buy product usually influence by some factors. It is important to know the factors that will influence customer intention to buy especially for new product likes Amanah Saham 1 Malaysia. This information will help organization (ASNB) to capture the factors that will attract customer to buy Amanah Saham 1 Malaysia. This study have been conducted to know the potential customer intention to buy Amanah Saham 1 Malaysia. This study is starting with the introduction of the company the problem statement, research question and research objective to make the research becoming more clear. After this, followed by the literature review that show the sources that researcher use in doing the research. In chapter 3, researcher identify the research methodology such as the sampling technique that researcher use, instrument used to capture information and the data collection analysis. Then, about the finding of the study. Last but not least the conclusion and recommendation for this study.